Municipal Refuse Disposal / Prepared by the Institute for Solid Wastes of American Public Works Association: Third Edition - Public Administration Service (1970)
Assistance by the Bureau of Solid Waste management U.S. Department of Health, Education and Welfare. Foreword, Preface, Institute for Solid Wastes, American Public Works Association, Introduction, Quantities and Composition of Refuse, Selecting Disposal Methods, Sanitary Landfills, Central Incineration, On-Site Incineration, Grinding Refuse, Feeding Food Wastes to Swine, Composting, Salvage and Reclamation, Refuse Disposal Management, Appendixes, Selected Bibliography, Index.